Evaluation of the AnaeroPack system for growth of anaerobic bacteria. - Van Horn, K G (1997)
Growth of anaerobic bacteria in the AnaeroPack (Mitsubishi Gas Chemical America, Inc., New York, N.Y.) anaerobic atmosphere generation systems, both the AnaeroPack jar and pouch and the AnaeroPack in a GasPak jar were considered equivalent to or better than growth obtained in the corresponding GasPak jar or pouch system (Becton Dickinson Microbiology Systems, Cockeysville, Md.) for 89 (86%) of the 103 anaerobes tested. There were a total of 26 discrepancies after 48 h of incubation, with 16 discrepancies unresolved after 96 h of incubation. The AnaeroPack jar and pouch never failed to reduce the anaerobic indicator. The AnaeroPack systems are easy to use and performed at least as well as or better than the BBL GasPak systems for growth of anaerobic bacteria.